Pencegahan Penularan Covid-19 pada Ibu Hamil/Ibu Bersalin : Prevention of Covid-19 Transmission to Pregnant Women/Maternity Women - Abdillah, Azhar Pherdinand; Al-Fajr, Sayyed Muhammad; Nursehha, Siti (MPI Press, 2022)
Introduction: This research focuses on preventing the transmission of COVID-19 to pregnant women or mothers giving birth at BPM (Independent Practicing Midwives). It is known that pregnant women or women giving birth are among those who are very vulnerable to being exposed to COVID-19. Objective: This research aims to find out what factors influence services, what factors must be implemented during the COVID-19 pandemic, and what factors have been carried out by BPM (Independent Practicing Midwives) in complying with the health protocols provided by the government. Methods: The method used in this research is descriptive quantitative research, namely research carried out to describe a phenomenon. The data collection method presented in numerical form is secondary data collection (Simpenan Health Center Data) and primary data was collected using questionnaires from June to July 2021. Results: The research results show that the BPM (Independent Practicing Midwives) in the Simpenan District Health Center Work Area has carried out/implemented the protocol very well. However, it was also found that 16 (6.37%) pregnant women or women in labor were exposed to the COVID-19 virus out of a total of 521 pregnant women/mothers in labor. Conclusion: Pregnant women in the Simpenan sub-district area already understand how to prevent the transmission of COVID-19 to pregnant women. We also see that the BPM or Community Health Centers in the Simpenan sub-district area have implemented very good Health Protocols to prevent the transmission of COVID-19.